2019
DOI: 10.1039/c8na00296g
|View full text |Cite
|
Sign up to set email alerts
|

Probing surface states in C60decorated ZnO microwires: detailed photoluminescence and cathodoluminescence investigations

Abstract: ZnO/C60composites were studied by spectroscopic techniques, suggesting the possibility of controlling/tuning the emission outcome by changing the C60amount on the ZnO surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 62 publications
8
23
1
Order By: Relevance
“…This behavior was attributed to both ZnO surface defect passivation and charge transfer between the two materials. Indeed, the interaction between carbon-based materials and ZnO is widely affected by the properties of each component, which may differ considerably depending on the type of structures and synthesis methods, resulting in subsequent variation in the alignment of the energy levels of both materials, namely the defect-related ones, leading to different luminescence features 33 , 75 .…”
Section: Resultsmentioning
confidence: 99%
“…This behavior was attributed to both ZnO surface defect passivation and charge transfer between the two materials. Indeed, the interaction between carbon-based materials and ZnO is widely affected by the properties of each component, which may differ considerably depending on the type of structures and synthesis methods, resulting in subsequent variation in the alignment of the energy levels of both materials, namely the defect-related ones, leading to different luminescence features 33 , 75 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, combining ZnO and LIG produced simultaneously by direct laser scribing showed that when the ZnO structures were produced from metallic zinc, the PL spectra displayed a weak luminescence signal, comprised by an orange/red emission band and with a very small contribution from the NBE emission, comparable to the spectral features observed herein 32 . Indeed, the interaction between carbon-based materials and ZnO is widely affected by the properties of each component, which may differ considerably depending on the type of structures and synthesis methods, resulting in subsequent variation in the alignment of the energy levels of both materials, namely the defect-related ones, leading to different luminescence features 32,73 .…”
Section: Photoluminescence and Photoluminescence Excitationmentioning
confidence: 99%
“…3,[14][15][16][17][18][19] Doping effects, thermal treatments under different atmospheres and coverage of as-grown micro-and nano-ZnO surfaces with continuous dielectric media are known to result in strong modications in the electronic energy levels inside the bandgap and band structure of the semiconductor oxide, with a notable inuence on the optical and electrical material response. 15,[20][21][22][23] In the case of ZnO, which has one of the largest free exciton binding energy values ($60 meV 23,24 ), a bandgap energy of $3.4 eV (at low temperature 23,25 ) and an exciton Bohr radius of $1.8 nm, 23,26,27 surface-related inuence has been reported in several optical studies, from cleaved bulk samples 28 to low dimensional structures. 20,[29][30][31][32][33] Additionally, decorating ZnO micro-and nanostructures with other metal oxides is known to result in numerous heterojunctions with enhanced properties, as in the case of gas sensor applications.…”
Section: Introductionmentioning
confidence: 99%